2020
DOI: 10.1049/iet-com.2019.0503
|View full text |Cite
|
Sign up to set email alerts
|

Network coding schemes with efficient LDPC coded MIMO–NOMA in two‐way relay networks

Abstract: The combination of non-orthogonal multiple access (NOMA) and multi-input multi-output (MIMO) approaches has been considered as assuring multiple access for the fifth generation technology. In this study, the performance of a 2 × 2 MIMO-NOMA system with low-density parity check (LDPC) codes is investigated. Redundancy with randomly interleaved differential encoding (R-RIDE) is proposed and applied to LDPC encoded messages by two users. LDPC decoding is done using the sum-product algorithm (SPA), which has two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Ferrett and Valenti [17] and Xie et al [19], the performance analysis focused on the uplink transmission only. Furthermore, LDPC-PLNC was presented with a 2×2 MIMO system and non-orthogonal multiple access (NOMA) [20]. Simulation results showed that the performance of the proposed LDPC with the MIMO-NOMA system greatly outperformed conventional LDPC-coded schemes in both NOMA and MIMO-NOMA systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrett and Valenti [17] and Xie et al [19], the performance analysis focused on the uplink transmission only. Furthermore, LDPC-PLNC was presented with a 2×2 MIMO system and non-orthogonal multiple access (NOMA) [20]. Simulation results showed that the performance of the proposed LDPC with the MIMO-NOMA system greatly outperformed conventional LDPC-coded schemes in both NOMA and MIMO-NOMA systems.…”
Section: Introductionmentioning
confidence: 99%